2007
DOI: 10.1080/87565640701360981
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Executive Functioning and Symptoms of Attention Deficit Hyperactivity Disorder on Children's Peer Relations and School Performance

Abstract: This study examined the predictive relations from symptoms of Attention-deficit/hyperactivity disorder (ADHD) and executive functioning (EF) to social and school functioning in 112 (62 girls) school children. High levels of teacher and parent ratings of ADHD symptoms at the ages of 8-8 1/2 years, and poor EF measured at the age of 8 1/2, were associated with poor social functioning measured by peer nominations and poor teacher ratings of school functioning at the age of 9 1/2. ADHD symptoms independently predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
176
4
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(205 citation statements)
references
References 53 publications
20
176
4
5
Order By: Relevance
“…Current evidence pertaining to the role of executive-skills deficits in explaining the social problems of children with ADHD is limited and inconsistent (Clark, Prior, & Kinsella, 2002;Diamantopoulou, Rydell, Thorell, & Bohlin, 2007;Huang-Pollock, Mikami, Pfiffner, & McBurnett, 2009). Although our study was not designed to test Barkley's (1997) theory, our current results could be interpreted as partly in line with some of his contentions.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Current evidence pertaining to the role of executive-skills deficits in explaining the social problems of children with ADHD is limited and inconsistent (Clark, Prior, & Kinsella, 2002;Diamantopoulou, Rydell, Thorell, & Bohlin, 2007;Huang-Pollock, Mikami, Pfiffner, & McBurnett, 2009). Although our study was not designed to test Barkley's (1997) theory, our current results could be interpreted as partly in line with some of his contentions.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…However, not all CD studies report these impairments [Fairchild et al, 2009;Pennington and Ozonoff, 1996]. The variation in results may be due to the fact that CD is often comorbid with ADHD, yet studies seldom examined their comorbidity [Déry et al, 1999;Diamantopoulou et al, 2007;Séguin et al, 2004Séguin et al, , 2009Waschbusch, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Extending previous research which concentrated on general social functioning and peer 309 status (Abikoff et al 2004;Bagwell et al 2001;Diamantopoulou et al 2005Diamantopoulou et al , 2007 Step 1: R 2 =0.033, p<0.01;…”
mentioning
confidence: 99%
“…Many studies have suggested that ADHD symptoms can be associated with difficulties 60 in peer relationships (Diamantopoulou et al 2005(Diamantopoulou et al , 2007. Children with ADHD symp-61 toms were found to be rejected and neglected by peers (Abikoff et al 2004;Bagwell et al 62 2001; Blachman and Hinshaw 2002 Furman 1996 (Berndt and Keefe 1995;Ladd et al 1996;Noakes and Rinaldi 2006).…”
mentioning
confidence: 99%